Alite dissolution and C-S-H precipitation rates during hydration. (January 2019) - Naber, C.; Bellmann, F.; Sowoidnich, T.; Goetz-Neunhoeffer, F.; Neubauer, J.
Abstract: An extensive dataset suitable for kinetic calculations was collected for the hydration of monoclinic alite at water to solid ratios of 10 and 0.5. The measurement methods used to investigate the hydration behavior are XRD, TGA, solid state NMR, BET, SEM and ICP-OES. A comparison of the two water to solid ratios shows only minor effects of the w/s-ratio on the reaction kinetics. Reaction rates for the two kinetic steps alite dissolution and C-S-H precipitation are calculated from this dataset and compared to the measured reaction rates. Computed reaction rates from C-S-H precipitation show a good match with the measured reaction rates, indicating that the computation incorporates all relevant factors related to C-S-H precipitation kinetics during hydration.